2007
DOI: 10.1093/ajcn/86.3.645
|View full text |Cite
|
Sign up to set email alerts
|

Safety of vitamin D3 in adults with multiple sclerosis

Abstract: Patients' serum 25(OH)D concentrations reached twice the top of the physiologic range without eliciting hypercalcemia or hypercalciuria. The data support the feasibility of pharmacologic doses of vitamin D3 for clinical research, and they provide objective evidence that vitamin D intake beyond the current upper limit is safe by a large margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
1
6

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 43 publications
7
150
1
6
Order By: Relevance
“…A few studies indicate that treatment with vitamin D could be beneficial as well in reducing the risk of developing MS and diminishing exacerbations of MS in affected patients [37;38]. In addition, a small 28-week trial in which MS patients received 28,000 to 280,000 IU/week provided evidence that high-dose vitamin D supplementation is safe in these patients [39]. Although contradictory data exist concerning supplementation benefits in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), an association between low levels of 25(OH)D and SLE disease activity [40] or RA disease activity [41] has recently been shown.…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 99%
“…A few studies indicate that treatment with vitamin D could be beneficial as well in reducing the risk of developing MS and diminishing exacerbations of MS in affected patients [37;38]. In addition, a small 28-week trial in which MS patients received 28,000 to 280,000 IU/week provided evidence that high-dose vitamin D supplementation is safe in these patients [39]. Although contradictory data exist concerning supplementation benefits in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), an association between low levels of 25(OH)D and SLE disease activity [40] or RA disease activity [41] has recently been shown.…”
Section: Vitamin D and The Immune Systemmentioning
confidence: 99%
“…One small safety study of 12 patients taking 1000 g per day (40,000 IU) of vitamin D for 28 weeks showed a decline in the number of gadolinium-enhancing lesions on magnetic resonance imaging per patient; this led to a 25(OH)D serum concentration of 386 nmol/L (158 ng/mL) without causing hypercalcemia, hypercalciuria, or other complication. 43 …”
Section: Vitamin D and Multiple Sclerosismentioning
confidence: 99%
“…However, the abundance of studies pointing at association of low vitamin D concentration and MS advocate for the beneficial role of vitamin D supplements as prophylactic and/or treatment agents. Clinical studies have indicated that large doses of 25(OH)D [79] and 1,25(OH)D [80] supplements are safe and well tolerated by MS patients. Even though disease progression and activity were not altered by 25(OH)D, the vitamin supplementation lead to reduction in gadolinium-enhancing lesions per patient as described by Kimball et al [79].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Clinical studies have indicated that large doses of 25(OH)D [79] and 1,25(OH)D [80] supplements are safe and well tolerated by MS patients. Even though disease progression and activity were not altered by 25(OH)D, the vitamin supplementation lead to reduction in gadolinium-enhancing lesions per patient as described by Kimball et al [79]. The therapeutic effects of vitamin D supplements are currently being further investigated.…”
Section: Vitamin Dmentioning
confidence: 99%